CO2 emissions from China's iron and steel industry. (15th December 2016) - Xu, Wenqing; Wan, Bin; Zhu, Tingyu; Shao, Mingpan
Abstract: With the increasing concerns on the severity of climate change, CO2 emissions have become a serious problem in China because of the country's heavy reliance on fossil fuels as an energy source. Therefore, precise quantification of the CO2 emissions that occur in China is of serious concern. Although most studies focus on CO2 emissions from power plant and cement production, the emissions from iron and steel industry is not well researched. The iron and steel industries, the energy consumptions of which are high compared to the rest of the world, are confronted with an increasing demand to reduce CO2 emissions. Data on CO2 emissions derived from iron and steel-making is a basic requirement for a certificate of CO2 reduction. This is the first study to present an analysis of CO2 emissions from China's iron and steel industry, and we have estimated the direct emissions, including coal fired emission, non fossil fuel combustion emission and indirect emissions. Carbon flows from blast furnace and basic oxygen furnace steel-making systems are analyzed using Material Flow Analysis. The computation method of coal oxidation factors is built and used to estimate the CO2 emissions of China in 2011 based on the production data of twenty typical iron and steel enterprises. The types of coal involved in iron and steel-making systems include coking coal, sintering (pelletizing) coal and spray-blow coal. It was determined that the coal oxidation factors of coking coal, sintering coal and spray-blow coal are 0.9351, 0.9995, and 0.9745, respectively. Based on the consumption and emission factors of different types of coal used in iron and steel-making systems, the total quantity of CO2 emissions of China in 2011 was estimated to be 1336 million tons, which is 7.06% lower than the result calculated with the parameters offered by the Intergovernmental Panel on Climate Change, in which the contribution of coking coal is the largest at 79.2%. Highlights: The computation method for coal oxidation factors calculation using Material Flow Analysis was built. The coal oxidation factors of coking coal, sintering coal and spray-blow coal are calculated. The CO2 emissions from the iron and steel industry in China were estimated. The total quantity of CO2 emissions from iron and steel industry of China was estimated.